Full-Stack React - Wassell, Shaun (Addison-Wesley Professional, 2020)
13+ Hours of Video Instruction BuildFull-Stack Apps with MongoDB, Express, React, and Node.js In this LiveLessons video, Shaun Wassell covers the fundamentals of full-stack development with the MERN (MongoDB, Express, React, and Node.js) stack. For the full stack, developers need to make sure both front- and backend communicate well together. Toward that end, this video teaches you how everything works, what the key responsibilities of each component are, and how they flow together. Shaun addresses the key points for developers, with specific examples to demonstrate concepts. Learn to use MongoDB, Express, React, and Node.js (MERN) to create full-stack apps. MERN is currently the most popular stack for building full-stack web applications. It allows developers to quickly write entire applications,Äîfrontend, backend, and database,Äîusing only JavaScript. In this 13+ hour LiveLessons video, Shaun Wassell covers the fundamentals of full-stack development with the MERN stack. You can learn by doing, as Shaun walks you through five example projects of increasing complexity that demonstrate the many different aspects of full-stack application development. How do you ensure your applications are secure? How do you handle authentication in full-stack apps? These are all questions Shaun answers in this timely and practical LiveLessons video. At the end of this video, you'll have five portfolio pieces that you can use for full-stack job interviews. Access the supplemental resources for this LiveLesson at https://github.com/shaunwa/full-stack-react About the Instructor Shaun Wassell 's goal is to create a world where people are empowered to use programming as a way to solve meaningful problems,Äîa world where writing code is just as natural for most people as walking or breathing. To help make this a reality, Shaun has dedicated the past few years to helping people learn and master software-development skills through video courses, live training sessions, and one-on-one tutoring. Shaun has been programming since he was a kid, when creating video games was his gateway into the world of software. Since then, he's been fortunate enough to be a contributing member on many amazing software projects and work with some incredible mentors along the way. Skill Level Intermediate What You Will Learn Companies have realized that a relatively small team of full-stack developers (developers that work on all parts of a web application) can build and maint...